Intra- and intergenomic chromosomal pairing in artificially polyploidized elephant grass and pearl millet hybrids - Santos, Fernanda Motta da Costa; Torres, Giovana Augusta; Techio, Vânia Helena; Pereira, Antônio Vander; Davide, Lisete Chamma (Pesquisa Agropecuaria Brasileira, 2017)
The objective of this work was to evaluate, by genomic in situ hybridization (GISH), pairing configurations as potential indicators of recombination between chromosomes of different parental genomes, in two interspecific hybrids (elephant grass x pearl millet) artificially polyploidized. Anthers from young flower buds were used in the chromosomal preparations. The genomic probe was prepared with pearl millet DNA and labeled with biotin-16-dUTP by the nick translation reaction. Blocking DNA was prepared with genomic elephant grass DNA. The homoeologous intergenomic pairing, observed in the two hybrids, indicates the possibility of recombination between chromosomes of the parental genomes.